PEMIKIRAN PLURALISME GUSDUR - TAUFANI TAUFANI (Jurnal Dakwah Tabligh, 2018)
In Post New Order era, religous based radicalism are  increasingly strong in Indonesia, therefore, discussing Gus Dur’s thought on the issue of pluralism becomes relevant today. The study aims to explore the Gus Dur’s thought in defining pluralism. The method of writing was done by using a qualitative aproach and the analysis model was descriptive analysis. The existing data were collected by library research by reading the literatures related to Gus Dur’s thought. The result of this paper indicates that pluralism is an idea to celebrate the diversity in Indonesia because it is compatible with the teaching of Islam, Pancasila, and also Indonesian constitution. Pluralism does not mean that all religions are alike because every single religion has its own differences and uniqueness. Pluralism does not only talk about diversity itself but also how one actively gets involved within it. Finally this study proves that pluralism should be promoted to reduce the religious based radicalism nowadays.